When practice meets policy in mathematics education A 19 country/jurisdiction case study - Schmidt, William H.. (OECD Publishing, 2022)
The OECD Future of Education and Skills 2030 (E2030) project's overall goal is that of looking to the future in terms of how school curricula should evolve given the technological advances and other changes that societies are now facing. Towards that end, the E2030 project centres on the idea that education needs to equip students with the knowledge, skills, attitudes and values they need to become active, responsible and engaged citizens. Mathematics is considered a highly relevant subject for achieving the above stated goals, as such it requires further and more detailed analysis. As a result, it has been chosen as one of the E2030 project's subject-specific analyses. The project has been named the Mathematics Curriculum Document Analysis (MCDA) study as per the request of participating countries. This working paper presents the findings of the MCDA study, which involves participants from 19 countries and jurisdictions
Keywords: Education